Analisis Peran Pejabat Pembuat Komitmen (PPK) dalam Penanganan Keterlambatan Proyek Pembangunan Gedung Plaza Aspirasi - Ade Irfansyah; Satyanto Krido Saptomo; Moh. Yanuar Jarwadi Purwanto (Jurnal Sosial Teknologi, 2026)
The construction of the Plaza Aspirasi Building experienced significant delays due to the contractor's weak technical and managerial readiness, land issues that led to a 43-day work stoppage, and the contractor's unpreparedness to fulfill the implementation plan. This condition caused the progress deviation to continue to increase until the project entered the critical contract category. This study aims to analyze the role of the Commitment Making Officer (PPK) in handling delays. Project delays occurred due to two factors: excuseable delays such as land claims by residents and non-excuseable delays in the form of the contractor's inability to manage the work project. The results of the study indicate that the PPK has carried out its contract control function systematically through issuing warnings, temporary suspensions, evaluation meetings, implementing tiered SCM, cross-agency coordination, and providing opportunities for work completion. Overall, the impact of delays on the project is not only seen in time deviations, but also spreads to the internal costs of service providers, work quality, and the effectiveness of contract management.